THE DEVELOPMENT AND FORMS OF THE THEORY AND PRACTICE OF CONCEPTUALIZATION IN UZBEKISTAN - Ismatullayeva Nigora Mukhammadali kizi (Modern American Journals, 2025)
This article explores the theoretical foundations and practical applications of conceptualization in the Uzbek context. It analyzes the historical evolution of conceptualization theory, its current state in Uzbekistan, and the various forms it has taken in linguistic, cultural, and educational practices. The study draws on interdisciplinary perspectives, including linguistics, cognitive science, philosophy, and pedagogy, to evaluate how conceptualization contributes to scientific knowledge, language development, and socio-cultural transformation in Uzbekistan.
Keywords: conceptualization, cognitive linguistics, theory and practice, uzbekistan, cultural forms, pedagogy.